INFLUENCE OF NATURAL-CLIMATIC CONDITIONS ON FORMATION OF TECHNOLOGICAL POTENTIAL OF SOFT WHEAT GRAIN - Darigash Arynovna Shaimerdenova (Современная наука и инновации, 2022)
The statistical data of natural and climatic conditions of the main grain-producing region of Kazakhstan - Northern Kazakhstan were studied, and their influence on the indices of technological value and technological potential of soft spring wheat was established.